Impact of hydrogen-rich-oxygenated ethyl acetate usage as a dual fuel in diesel engines on combustion stability and exhaust emissions under varying EGR rates - Celebi, Samet; Gulcan, Halil Erdi; Özer, Salih; Celik, Hasan Ali; Demir, Usame (Elsevier Sci Ltd, 2026)
Diesel engines, due to their reliance on petroleum-derived fuels for power generation, not only emit high levels of nitrogen oxides and smoke but also contribute significantly to greenhouse gas emissions that drive climate change. Therefore, the use of alternative fuels has become essential to reduce dependency on petroleum-based fuels in these engines. Oxygenated fuels can be effective in minimizing emissions. In this study, ethyl acetate-which is rich in hydrogen and oxygen and considered a potential hydrogen carrier-is used in dual-fuel mode to improve combustion performance and reduce exhaust emissions. Experimentally, the effects of different exhaust gas recirculation rates and injection durations on the combustion and emission characteristics of a compression-ignition engine operating in a diesel-ethyl acetate dual-fuel mode are investigated. The exhaust gas recirculation rates vary as 0 %, 5 %, 10 %, and 20 %, while the ethyl acetate injection duration changes as 1 ms, 2 ms, and 3 ms. Additionally, experiments are conducted at different engine loads (5 kg, 10 kg, 15 kg, and 20 kg) and a constant engine speed of 1800 rpm. The results indicate that increasing the ethyl acetate injection duration reduces the maximum pressure at low loads but increases it at high loads. Moreover, the use of ethyl acetate increases the ignition delay by approximately 11 % and raises the cycle-to-cycle variation to around 23 %. Regarding emissions, increases in injection duration and exhaust gas recirculation rate reduce nitrogen oxides emissions by an average of approximately 39 % and smoke emissions by an average of around 75 %.
Keywords: Combustion; Emissions; Ethyl acetate; EGR rate; Injection duration